Morphology of the urogenital papilla and its component ducts in Astyanax altiparanae Garutti & Britski, 2000 (Characiformes: Characidae) - de Siqueira-Silva, Diógenes Henrique [UNESP]; dos Santos Silva, Amanda Pereira [UNESP]; Ninhaus-Silveira, Alexandre [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP] (FapUNIFESP (SciELO), 2015)
The histological description of the urogenital papilla is an important tool to comprehension of the reproductive mechanisms in fish, as well as a pre-requisite to germ cell transplantation in adult fish, besides to be a good biological indicator to environmental changes. Was performed the histological description of the urogenital papilla and its component ducts in the tetra Astyanax altiparanae. The genital and urinay ducts pass separately throughout most part of its extension, joining in a single duct before opening. In males this opening is asymmetric and seems to have double origin, being completely surrounded by striated muscle fibers, while in females it is symmetric and the muscle fibers does not surround it totally. Spermatic duct and oviduct undergo changes throughout their extension, mainly in the morphology of the surrounding epithelium. In the spermatic duct, squamous epithelial cells change to columnar and cuboid with possible secretory activity, close to testes. In the oviduct, anteriorly epithelial cells are also squamous, however, close to ovary there are lamellae composed by a pseudostratified epithelium with columnar and cuboid cells. The urinary duct is highly similar for both sexes presenting globoid cells, which description is known in mammals, however, rare in fish.
Keywords: Fish reproduction; Histological analysis; Oviduct; Sperm duct; Urinary duct